SimNerv : multimedia simulation of the frog nerve experiment - Hirsch, Martin Christian (Stuttgart : Georg Thieme Verlag, 1998)
This interactive multimedia serves as an intruduction to the basic elements of electrophysiology by students to observe the reaction of the nervus ischiadicus to different stimulation and sequences and draw comclusion regarding the basic properties of nerves.
System requirements : IBM-compatible PC 80486 processor; 8 MB RAM in addition to the RAM requirements for the system; Windows 3.1 or higher; 256 colors at 640 x 480 resolution, 2 x CD-RON drive; sound card
System requirement : 68030 processor ; CD-ROM Drive ; 8 MB RAM in addition to the RAM requirements for the system; 256 colors at 640 x 480 resolution, 2 x CD-ROM drive
Keywords: Sciatic Nerve -- physiology; Anura; Electrophysiology